(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article is devoted to comparative study of literary biography and memoirs as kinds of the documentary literature. Their general and different typological traits are analyzed too. The author of the article investigates the process of crossing of literary biographical and memoirs discourse in text level of literary biography, changes of text narrative techniques by reason of author’s invasion of literary biographical story space.